PASAR PERSAINGAN SEMPURNA DAN MONOPOLI - Ahmad_Khusnul_Hakim; Elmuna, Naily; Suprayogi, Agus (LPPM Universitas KH. A. Wahab Hasbullah, 2020)
Abstract: This research describes the structure between the perfect competition market and the imperfect competition market which is also seen from an Islamic perspective, which of course also talks about the structure of the perfect competition market and imperfect competition market, as well as several things about this. Market, which incidentally is a meeting place for buyers and sellers to carry out buying and selling transactions of goods and services, as well as a place for the community to meet the needs and drivers of the community's economy. In this report, some information is generated regarding the two types of markets, such as the meaning, differences in the perfect competition market and imperfect competition market, the advantages and disadvantages of perfect and imperfect competition markets, market mechanisms, etc. The data collection method used in this study was to collect data from related web literature studies Keywords: Perfect competition market, imperfect competition market, market mechanism.